2007
DOI: 10.1016/j.febslet.2007.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of RVV‐X: An example of evolutionary gain of specificity by ADAM proteinases

Abstract: RussellÕs viper venom factor X activator (RVV-X) is a heterotrimeric metalloproteinase with a mammalian ADAM-like heavy chain and two lectin-like light chains. The crystal structure of RVV-X has been determined at 2.9 Å resolution and shows a hook-spanner-wrench-like architecture, in which the metalloproteinase/disintegrin region constitutes a hook, and the lectin-like domains constitute a handle. A 6.5 nm separation between the catalytic site and a putative exosite suggests a docking model for factor X. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 21 publications
2
73
0
1
Order By: Relevance
“…Despite their divergent nomenclature, accumulating evidence suggests the catalytic domain and Dis-Cys domain are spatially associated within the complete ADAM ectodomain (14,15). Specifically, the crystal structures of ADAM homologs VAP1 (13), VAP2B (16), RVVX (17), and the nonproteolytic ectodomain of human ADAM22 (18) support the notion that ADAM proteins are "C-shaped" (Fig. S1).…”
Section: Adam17 | Antibody Phage Display | Cancer Therapeuticsmentioning
confidence: 65%
“…Despite their divergent nomenclature, accumulating evidence suggests the catalytic domain and Dis-Cys domain are spatially associated within the complete ADAM ectodomain (14,15). Specifically, the crystal structures of ADAM homologs VAP1 (13), VAP2B (16), RVVX (17), and the nonproteolytic ectodomain of human ADAM22 (18) support the notion that ADAM proteins are "C-shaped" (Fig. S1).…”
Section: Adam17 | Antibody Phage Display | Cancer Therapeuticsmentioning
confidence: 65%
“…Although currently there are only a few reports of potential exosites in ADAM protease structures (11,31), a recent paper by Tape et al (32) demonstrated that it is possible to achieve selective binding to the ADAM17 ectodomain by an antibody that exploits exosites. Our group recently reported a discovery of a small molecule that inhibits ADAM17 in a non-zinc-binding fashion, which also supports exosite targeting strategies for ADAM17 drug and probe discovery (15).…”
mentioning
confidence: 99%
“…Crystallographic and modeling studies by Takeda et al (10,11), demonstrated the possibility that noncatalytic domains of membrane-bound ADAM17 can contribute to substrate recognition and binding of cell surface proteins, which necessitates studies with substrates that can interact with noncatalytic domains. Cleavage site sequence specificity has been addressed for several members of the ADAM family (12)(13)(14), but most of the substrates utilized for these studies were short (ϳ10 residues) and therefore were likely to interact only with the catalytic domain of ADAMs.…”
mentioning
confidence: 99%
“…Indeed, D14 0 isoform lacks the hypervariable region, so the intact disintegrin domain would be more readily available to interact with an integrin molecule. In contrast, three-dimensional data suggest that the disintegrin domain in wild-type ADAM8 would be partially hidden by the hypervariable region (Takeda et al, 2007). These structural differences could explain the higher activity of the D14 0 isoform than the full-length isoform in the fusion of mononuclear precursors.…”
Section: Discussionmentioning
confidence: 93%